Understanding motivators and barriers for yoga practice in obese and non-obese individuals - Telles, Shirley; Gupta, Shivam K.; Sharma, Sachin K. (International Journal of Research in Medical Sciences, 2024)
Background: Yoga is a comprehensive lifestyle intervention which has been used for weight management by overweight and obese. Yoga is also used as therapy for various other ailments by both obese and non-obese individuals. However, the motivators and barriers of yoga in obese persons compared to non-obese has not been reported. Methods: The present cross-sectional comparative control trial included 200 participants of both sexes aged between 13 and 80 years. Of these, 102 were obese and 98 were non-obese. Data were analyzed using Chi-square test. Results: The most common motivators for yoga were: reducing symptoms of illness (35% for obese versus 21.73% for non-obese), pain relief, (21% for obese versus 10.86% for non-obese) and lifestyle changes (9% for obese versus 10.86% for non-obese). The most common barriers for yoga were: no time (29.54% for obese versus 42.25% for non-obese), physical incapability of practicing yoga (18.18% for obese versus 16.9% for non-obese) and tiredness (15.9%) for obese and no interest/motivation (15.49%) for non-obese. Conclusions: The motivators to yoga for obese are comparable to non-obese with obese use yoga more frequently for “reducing symptoms of illness”. Also, the barriers to yoga are comparable to obese with normal weight for “no time”.